From Sun 禪(zen) to Sun 線(line) to Sun 仙(transcendence): Interdisciplinary Exploration of Identity through Avant Garde Piano Performance - Park Atanassov, Grace Sun (Royal Irish Academy of Music, 2026)
This research explores how avant-garde piano performance serves as a medium for recreation of my artistic identity. This artistic research initially began with self examination of identity shaped by the experience of living in multiple countries and adopting diverse cultures that led to a complex sense of self. This developed into a research question: how can I convey my multicultural identity through piano performance? Thus, this research is grounded in an autoethnographical approach and examines the intersection between the subject of identity and piano performance. The research is grounded in the works of the avant-garde artists John Cage, Nam JunePaik and Margaret Leng Tan. I explore how these artists challenged the traditional boundaries and opened a new path of performance practice that express their own identities. I investigate theoretical frameworks on identity in the context of performance art by these artists. As a result, I experiment with various approaches to determine the most effective way to convey my personal identity exploration through avant garde music by incorporating multimedia strategies and unconventional ways of performing piano. This research explores reinvention of the role of a professionally-trained pianist, examining the themes of cultural dislocation and personal identity and embracing a process of re-education. The element of destruction in avant garde music leads to a reconstruction of my artistic identity and provides an opportunity to rethink the role of the pianist.
Keywords: HUMANITIES and RELIGION::Aesthetic subjects::Music; Performance practice (Music); Piano--Performance; Avant-garde (Music); Cage, John, 1912-1992; Paik, Nam June, 1932-2006; Tan, Margaret Leng